Peran Mediasi Burnout dalam Pengaruh Work-Life Balance dan Job Stress Terhadap Kinerja Karyawan dan Niat Pindah Kerja pada Industri Manufaktur di Kabupaten Tangerang, Banten - Inayatuddiniyah; Basuki Rahmat; Nafiz Annas; Feby Arma Putra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Productivity pressures, target-based work systems, shift arrangements, and high psychological demands make the manufacturing industry vulnerable to work-life balance issues and employee job stress. These conditions have the potential to reduce performance and increase turnover intentions, especially when they trigger burnout. This study aims to analyze the effect of work-life balance and job stress on employee performance and turnover intentions, with burnout as a mediating variable, among manufacturing industry employees in Tangerang Regency, Banten. The study used a quantitative explanatory approach with a survey method of 200 employees. Data analysis was conducted using multiple regression, path analysis, and bootstrapping mediation tests. The results showed that work-life balance reduces burnout and improves performance, while simultaneously suppressing turnover intentions. Conversely, job stress increases burnout and has an indirect impact on decreased performance and increased turnover intentions through burnout. Burnout has been shown to play a key mediator explaining the relationship between work-life balance, job stress, and work outcomes. These findings strengthen the relevance of Job Demands–Resources Theory in the context of the manufacturing industry. Practically, companies need to manage workloads, strengthen superior support, and implement burnout prevention strategies to maintain performance and reduce employee turnover.